Podstata variability úcinku hormónov stítnej zl'azy - Filipcík, P; Brtko, J (Ceskoslovenska fysiologie, 1996)
Among physiological reactions of the organism, the multiplicity of action of thyroid hormones is a well known phenomenon. Thyroid hormones (TH) regulate activity of other hormones, receptors for bioactive signals, enzymes, and the function of ion channels. Until triiodothyronine has been identified as a ligand for oncoprotein c-erbA, this broad potency of actions has been mysterious. C-erbA has been recognized to be a transcription factor and an authentic thyroid hormone receptor. Important evidence comes from molecular studies, which have described isoforms of c-erbA and other members of intranuclear receptor family, their heterodimerization, thyroid hormone responsive elements in the target genes, and the existence of the cross-talk mechanism. Till present, much has been learned about TH transcription regulations in vitro. An open question remains whether this regulations are operative also in the intact organism.
Keywords: Thyroid Hormones; Oncogene Proteins v-erbA; hormony štítné žlázy; zvířata; receptory thyreoidních hormonů; onkogenní proteiny v-erbA; trijodthyronin; Animals; Receptors, Thyroid Hormone; Humans; lidé; Triiodothyronine